Tantangan Dan Implementasi Pengembangan Kurikulum Pendidikan Agama Islam - Dudung Abdul Rahman (Tihamah: Jurnal Studi Islam, 2023)
Islamic religious education is still at the understanding process stage, not yet fully at the application stage. This study adopted a qualitative descriptive analysis method. The approach used in this study is the library research approach. the teacher is a "key factor" component in the development of the curriculum itself, especially in dealing with the dynamics of social change at this time, where teachers are required to keep abreast of technological developments, for the sake of continuity of educational interaction. The development of a well-implemented Islamic religious education curriculum will produce quality graduates, and of course have an impact on Islamic education institutions, of course with the support of teachers who are not left behind in the progress and development of technology and information. The development of a well-implemented Islamic religious education curriculum will produce quality graduates, and of course have an impact on Islamic education institutions, of course with the support of teachers who are not left behind in the progress and development of technology and information.